Corporate foundation’s relationship with the founding company and its role in image building and corporate community involvement programmes - Kwiecińska, Monika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The research presented in this article analyses the mutual relations between corporate foundations and their founding companies, as well as the roles foundations play in building the company’s image and CCI programmes. In order to achieve this goal, the author presents selected theoretical approaches and own research results that were part of a project entitled Corporate foundation as a tool for realizing the company’s social goals, financed by the National Science Centre in Krakow
Argumenta Oeconomica, 2015, Nr 2 (35), s. 169-184
Keywords: Corporate Community Involvement; corporate reputation; public relations; corporate fundation